Dynamics of Child Custody from the Perspective of Islamic Family Law in the Digital Age: Challenges and Solutions - Shobichah, Shobichah (Journal of Islamic Family Law, 2025)
The advancement of digital technology has significantly transformed the dynamics of Muslim family life, particularly in child custody issues after divorce. New challenges emerge as parents are required not only to fulfill the physical and emotional needs of the child but also to ensure their safety in digital spaces. However, Islamic family law in Indonesia, as codified in the Compilation of Islamic Law (KHI), has yet to address digital dimensions in child custody arrangements specifically. This research aims to reassess the concept of child custody within Islamic family law, incorporating digital-age challenges, and to formulate practical solutions based on the principles of maqasid al-shariah. Employing a normative juridical and empirical sociological approach, this research gathers data through literature review, in-depth interviews, questionnaires, and field observations involving 30 post-divorce families from urban and semi-urban areas. Findings reveal that most custodial parents exhibit low to moderate levels of digital literacy, which weakens their ability to supervise children's online activities effectively. From a normative perspective, the absence of digital competence indicators in custody rulings creates a legal and protective gap for children. This research proposes a Digital-Responsive Custody Framework as an alternative model for Islamic family law that is more aligned with contemporary challenges.